BENTUK DAN CIRI ADJEKTIVA BAHASA DAYAK NGAJU - Elisten Parulian Sigiro (Balai Bahasa Nusa Tenggara Barat, 2016)
The method used in this research is descriptive qualitative methods and techniques in this study reflect the reality on the facts (fact findings) that is in the field as it is. This research examines how the shape and characteristics of adjectives in BDNg. Thus, the researchers sought to describe objectively and accurately in accordance with the aspects of adjectives BDNg current conditions. In practice, this is done through two methods of data collection techniques, namely by using interview and documentation techniques. The findings of this research, that adjective BDNg can be marked by characteristic, namely (1) there is a possibility to join the particle beken 'not' and dia 'no' (2) can accompany a noun, or (3) may be accompanied by words labih 'more' , pangka 'most', tutu 'very', and labien 'very'. Meanwhile, based on variations in shape, adjectives can be distinguished BDNg its kind on the basis adjectives and adjectival derivative. Basic adjectives are adjectives that only consist of a single morpheme. Meanwhile, the derivative adjective derivative form BDNghave formed through the process of moving on word class and morphological processes, namely affixation, reduplication and compounding. Based their category, there is only one category of adjectives of adjectives BDNg, the adjectives predicative (adjectives that could occupy the position of the predicate in the clause). Furthermore, in its formation, adjectives BDNg formed through some process of affixation, reduplication and compounding.